2012
DOI: 10.1071/sr11104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of afforestation with Eucalyptus grandis on soil physicochemical and microbiological properties

Abstract: It is generally believed that plantations of Eucalyptus bring about a decrease in soil fertility. Soil physicochemical and microbiological properties were measured across a range of E. grandis plantation ages (1–10 years) in south-western China to determine whether and how eucalypt afforestation of agricultural land affected the soil fertility. The results indicate that afforestation with E. grandis caused changes in soil properties with soil depth, and the changes were dependent on the stand age. Soil bulk de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 38 publications
2
15
1
1
Order By: Relevance
“…In general, the results show that soil enzymatic activities reaches the values observed in the native forest after 3 years of plantation, indicating improvement of these properties with time of reforestation. The results obtained in our work and that of Zhang et al (2012) contrast with the general ideas about negative short-time effects of Eucalyptus plantation in the soil. In a more recent paper, Zhang et al (2015) observed that converting Pinus to Eucalyptus plantations produced a significant decrease in soil quality in the first and second generations, but the soil partially recovered in the following third and fourth generations.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In general, the results show that soil enzymatic activities reaches the values observed in the native forest after 3 years of plantation, indicating improvement of these properties with time of reforestation. The results obtained in our work and that of Zhang et al (2012) contrast with the general ideas about negative short-time effects of Eucalyptus plantation in the soil. In a more recent paper, Zhang et al (2015) observed that converting Pinus to Eucalyptus plantations produced a significant decrease in soil quality in the first and second generations, but the soil partially recovered in the following third and fourth generations.…”
Section: Discussioncontrasting
confidence: 99%
“…The results obtained in our work and that of Zhang et al . () contrast with the general ideas about negative short‐time effects of Eucalyptus plantation in the soil. In a more recent paper, Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The microenvironment in a Eucalyptus plantation improves gradually with increasing age. Soil physical traits such as SBD and soil water content will be ameliorated (Zhang et al ; Wu et al ). The available N, P, K, and cation exchange capacity in the upper soil will be improved (Mohsin et al ; Zhang et al ), and the soil microbial biomass C and N concentrations will also increase accordingly (Zhang et al ), as well as the arbuscular mycorrhizae (Wu et al ).…”
Section: Discussionmentioning
confidence: 99%
“…The soil properties of former cropland in secondary forest are slowly modified towards conditions found in native forests because of a lack of intense cultivation (i.e. high fertilization rates, annual tillage, weed control) along with progressive vegetation succession (Zhang et al 2012). In the initial phase of regeneration, former cultivated land retains an increased N status as a legacy of former fertilization, which supports persistent, relatively increased rates of mineralization and nitrification (Jug et al 1999) but which is predicted to change over time as the source of N in soils switches from inorganic fertilisers to biological fixation.…”
Section: Response Of Soil Functions To Agricultural Abandonment Undermentioning
confidence: 99%